Coreceptor Usage by HIV-1 and HIV-2 Primary Isolates: The Relevance of CCR8 Chemokine Receptor as an Alternative Coreceptor - Calado, M (2014)
The human immunodeficiency virus replication cycle begins by sequential interactions between viral envelope glycoproteins with CD4 molecule and a member of the seven-transmembrane, G-protein-coupled, receptors' family (coreceptor). In this report we focused on the contribution of CCR8 as alternative coreceptor for HIV-1 and HIV-2 isolates. We found that this coreceptor was efficiently used not only by HIV-2 but particularly by HIV-1 isolates. We demonstrate that CXCR4 usage, either alone or together with CCR5 and/or CCR8, was more frequently observed in HIV-1 than in HIV-2 isolates. Directly related to this is the finding that the non-usage of CXCR4 is significantly more common in HIV-2 isolates; both features could be associated with the slower disease progression generally observed in HIV-2 infected patients. The ability of some viral isolates to use alternative coreceptors besides CCR5 and CXCR4 could further impact on the efficacy of entry inhibitor therapy and possibly also in HIV pathogenesis.